IMPACT OF DRILLING WASTE ON HYDROBIONTS - S. A. Guseinova (Юг России: экология, развитие, 2015)
Aim. The aim is to determine and make an analysis of the concentration of petroleum hydrocarbons and other metals in the waste drilling: drill cuttings (DC) and mud (DM), collected in the area of drilling, to assess and forecast the state of biological resources of natural sea water.Methods. Experimental studies of DC and DM showed the petroleum hydrocarbons content, the concentration of which varies depending on the timing of exposure. By quantitative and qualitative indicators, the metal content in the drill cuttings and mud is nonequivalent and this depends on the structure and hardness achieved during drilling the rocks as well as on the degree of contamination with metals.Results. The concentration level of petroleum hydrocarbons and other metals in the drilling waste (drill cuttings and mud) imposes a major problem associated with the conservation of biological resources of the Caspian Sea.Main conclusions. Environmental effects from the discharges of drilling waste on the high seas can be detected only during drilling operations and in close proximity (typically up to 200-500 m) from the discharge point. Persistent damages in communities and ecosystems occur only at long exposures and are adaptive in nature.